Analisis Putusan Hakim tentang Penolakan Permohonan Itsbat Nikah (Putusan No. 47/Pdt.P/2021/PA.Tas Hakim Pengadilan Agama Tais) - Putri, Alifia Meita; Muslih, Muhamad (Universitas Sultan Ageng Tirtayasa, 2023)
The problem in this research is that Article 2 paragraph 2 of Law no. 16 of 2019 concerning Amendments to Law no. 1 of 1974 concerning Marriage states that every marriage must be recorded according to the applicable laws and regulations, so that if there is an underhand marriage, the marriage certificate must be submitted, but in the judge's decision No. 47/Pdt.P/2021/PA.Tas the judge of the Tais Religious Court rejected the submission of the marriage certificate. Identification of the problem in this study, namely what are the judges' considerations at the Tais Religious Court in rejecting the application for itsbat nikah? So what are the legal consequences for underhanded marital status and child status? The research method used is normative juridical, with a statutory approach and a case approach. The theory used in this study is the theory of legal certainty and the theory of justice. The data source is secondary data, with the technique of collecting data from the study of literature and analyzing the data used, namely descriptive qualitative. The conclusion of this study is the rejection of the marriage certificate by the judge on the grounds that there is no good faith from the applicant so that this causes the applicants to not get legal certainty regarding marital status and child status. The legal consequence of the rejection of the application for itsbat nikah makes the marital status of the applicants remain in the status of underhanded marriage and the status of the child becomes a child out of wedlock.